Better monitoring ...Worse outcome? - Zhu, John Y. (RAND Journal of Economics (Wiley-Blackwell), 2024)
New technologies allow firms to collect more information about worker performance than ever before. How will this extra information—much of which is non‐contractible and is used at the firm's discretion—impact incentives? I highlight a better monitoring/worse outcome channel that speaks to these concerns. Some improvements to monitoring tempt the firm to punish excessively. Workers then demand contracts with a small punishment threat. Without a serious punishment threat, effort and surplus decline. I characterize what kinds of improvements to monitoring lead to a worse outcome and explore how technologies can be designed to mitigate the better monitoring/worse outcome effect.